2014
DOI: 10.1007/s11060-014-1464-8
|View full text |Cite
|
Sign up to set email alerts
|

Histogram analysis of apparent diffusion coefficient within enhancing and nonenhancing tumor volumes in recurrent glioblastoma patients treated with bevacizumab

Abstract: While patients with recurrent glioblastoma receiving anti-angiogenic therapy demonstrate significant response rates, the benefit on patient survival is less clear. We assessed whether histogram analysis of diffusion weighted MRI can stratify for progression-free and overall survival. Baseline and 3-6 week post-treatment MRI exams of 91 patients with recurrent glioblastoma treated with bevacizumab were retrospectively evaluated. Histograms of apparent diffusion coefficient (ADC) within the volume of contrast en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 21 publications
0
47
1
2
Order By: Relevance
“…Pope et al 34 investigated low ADC values through histogram analysis and agreed with the conclusion that low values indicated areas of hypercellularity. Other studies, however, have hypothesized that these regions could not correspond to tumor because not all patients progressed 35,36 . They instead hypothesized that these regions would most likely be chronic hypoxia and necrosis 36 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Pope et al 34 investigated low ADC values through histogram analysis and agreed with the conclusion that low values indicated areas of hypercellularity. Other studies, however, have hypothesized that these regions could not correspond to tumor because not all patients progressed 35,36 . They instead hypothesized that these regions would most likely be chronic hypoxia and necrosis 36 .…”
Section: Discussionmentioning
confidence: 95%
“…Other studies, however, have hypothesized that these regions could not correspond to tumor because not all patients progressed 35,36 . They instead hypothesized that these regions would most likely be chronic hypoxia and necrosis 36 .…”
Section: Discussionmentioning
confidence: 95%
“…Functional diffusion maps (fDMs) [75] and histogram analysis need [86] to be highlighted. These techniques, which apply ADC maps to characterize the heterogeneity of therapy response, have been used to evaluate the efficacy of cytotoxic and antiangiogenic therapies [85, 87, 88]. …”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…In this way, texture features can be a proxy to quantifying intra-tumoral heterogeneity. In fact, texture features seem to be amongst the most promising features in terms of prognosis [49,55,74,75]. First-order statistics and texture features are often also extracted after filtering methods, such as wavelets or Laplace of Gaussian, have been applied to the original image.…”
Section: ) Image Acquisitionmentioning
confidence: 99%
“…For example, recent studies have suggested that apparent diffusion coefficient histogram analysis has prognostic value in a subset of the BRAIN cohort [54,55]. Similarly, FDG-PET imaging could predict survival in high-grade gliomas treated with the same combination therapy as in the BRAIN trial [56].…”
Section: Imaging Biomarkers To Stratify Recurrent Glioblastoma Treatementioning
confidence: 99%